The contribution of GLONASS measurements to regional and continental scale geodetic monitoring regimes - Stewart, M. P.; Tsakiri, M.; Wang, J.; Monico, J. F. [UNESP] (Springer Nature, 2000)
Throughout late 1998 and early 1999, the International GLONASS Experiment (IGEX) has delivered the first comprehensive inter-continental dual frequency GLONASS data set. This experiment represents the first opportunity to assess how a second global satellite positioning system could complement existing GPS geodetic infrastructure. Based on analysis of a three station network of IGEX stations from Southern Hemisphere IGEX stations, this paper discusses the internal and external precision of long baseline GPS, GLONASS and combined GPS/GLONASS solutions, and the possible contribution of GLONASS to future regional-scale geodetic work. Copy right©The Society of Geomagnetism and Earth, Planetary and Space Sciences (SGEPSS); The Seismological Society of Japan; The Volcanological Society of Japan; The Geodetic Society of Japan; The Japanese Society for Planetary Sciences.